Staff Profile: Dr. Johana Kambo Gathongo - Gathongo, Johana K. (University of Embu, 2019)
Dr Johana Kambo Gathongo is Dean, School of Law at the University of Embu. He teaches Tort Law and Legal Research and Writing. Research Interests His research is situated in the field of Law, with a special focus on Labour Law.